2016
DOI: 10.3329/jpsb.v6i1.27741
|View full text |Cite
|
Sign up to set email alerts
|

Gender Specific Psychological Distress in Cancer Patients with Underage Children

Abstract: Background: Psychological distress has become an epidemic among cancer patients. Less is known about the pattern of anxiety and depression in cancer patients with minor children. Gender issue is also important in this regard. Psychological distress is an important predictor of quality of life in cancer patients. A majority of these disorders are eminently treatable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…Of those, we included 39 publications for the synthesis of findings on the levels and prevalence of mental burden (second research question). Studies were excluded at the stage of synthesis for the second research question, if included data had already been reported in another publication with a more comprehensive sample derived from the same study 13,21‐32 . Publications based on the same study were only included, if they reported any additional results with relevance to the research questions of this systematic review.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of those, we included 39 publications for the synthesis of findings on the levels and prevalence of mental burden (second research question). Studies were excluded at the stage of synthesis for the second research question, if included data had already been reported in another publication with a more comprehensive sample derived from the same study 13,21‐32 . Publications based on the same study were only included, if they reported any additional results with relevance to the research questions of this systematic review.…”
Section: Resultsmentioning
confidence: 99%
“…Studies were excluded at the stage of synthesis for the second research question, if included data had already been reported in another publication with a more comprehensive sample derived from the same study. 13,[21][22][23][24][25][26][27][28][29][30][31][32] Publications based on the same study were only included, if they reported any additional results with relevance to the research questions of this systematic review.…”
Section: Study Selectionmentioning
confidence: 99%
“…In line with this hypothesis, a study carried out in families of children with cancer highlighted that the time since the diagnosis positively moderated the effect of parental depression on child's anxiety, so that parents' and children's symptoms were more strongly associated in families with a greater amount of time elapsed since the diagnosis [35]. It could also be hypothesized that an oncological diagnosis is an ongoing problem [36] with long-term outcomes [37] that affect not only the patient but also the whole family [3]. However, we may not exclude that other factors not explored in the present research may contribute to this finding.…”
Section: Discussionmentioning
confidence: 97%